PENGARUH PROFITABILITAS, KEPEMILIKAN KELUARGA, CORPORATE GOVERNANCE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAAN PAJAK DI INDONESIA (Studi Empiris Perusahaan Manufaktur yang Listed di BEI tahun 2012-2014) - Dianing Ratna Wijayani (Jurnal Dinamika Ekonomi & Bisnis, 2017)
The purpose of this research was to determine the effect of profitability, family ownership, independent commissioner, institutional ownership against tax evasion (tax aovidence). The population of this research is manufacturing companies listed on the Stock Exchange in 2012-2014, the number of samples obtained by the sampling technique is purposive sampling as many as 54 companies. The type of data used is secondary data by using the method of data collection and documentation of ICMD IDX. The method of analysis in this research is multiple regression analysis.These results indicate that the effect on the profitability of tax avoidance (tax aovidence). Family ownership does not affect the tax evasion (tax aovidence). Independent commissioner significantly negative effect on tax evasion (tax aovidence). Institutional ownership has a significant influence on tax evasion (tax aovidence).